Evolution of mortality by prostate cancer in Colombia: An ecological study (2014)
Introduction and objectives: There is a worldwide increase in the incidence of prostate cancer, which is associated with longer life expectancy and the use of prostate-screening. Although mortality rates for prostate cancer mortality vary, it has become a public health problem. This study describes the development of prostate cancer mortality in Colombia at national and regional levels. Materials and methods: A mixed ecological study was developed, with three study levels: the country, its geographical regions and its departments. Time series have been created for the country between 1997 and 2012, regions and departments were followed between 2008 and 2012. Deaths related to the ICD-10 code C61 were included. Statistics databases for cancer mortality were reviewed from the National Administrative Department of Statistics records. Results: A national mortality rate between 8.9 and 10.9 per 100,000 men was found, in a time series. The Pacific and Andina regions have the highest regional mortality rates. The departments of Cesar and Valle have the highest department mortality rates. The standard national mortality rate was similar to other countries with similar socioeconomic characteristics. Conclusions: The mortality rate due to prostate cancer in Colombia has decreased in the last four years. Continued development of screening programs should be optimized for regions with rural population and black populations with higher prevalences, and where mortality rates are higher than average. © 2014 Sociedad Colombiana de Urología.